Green Marketing for People and Planet: 7Ps and Green Knowledge Impact on Nestlé Single-Use Plastic Water Bottle Repurchase Intentions in Pakistan (Journal of Asian Development Studies, 2025)
Pakistan is developing a National Plastic Action Partnership with the FMCG sector, bringing the "green" to the forefront of core marketing activities. The current study investigated how the 7Ps Green Marketing Mix (GMM) affects consumer repurchase intentions in Pakistan, specifically examining the role of green knowledge in the context of single-use plastic water bottles. Four hundred responses were collected through purposive sampling and analysed using SmartPLS SEM version 4. Results showed sufficient evidence of green knowledge enhancing the positive impact of GMM on consumers' repurchase intentions for responsible plastic bottle consumption. GMM influences consumer green knowledge by providing information, cues, and experiences, thereby enhancing their understanding of environmental issues and sustainable practices to achieve organisational goals while minimizing harm and promoting sustainable development goals. The GMM theory expanded our understanding of how effectively using the 7Ps can raise awareness of green knowledge, which is key to encouraging repurchase intentions. Incorporating green knowledge enriches this theory by recognising the importance of green marketing efforts in influencing favourable repurchase intention. From a practical standpoint, this research highlights the inclusive role of industry and consumers in effectively tackling the complex, conditional, and collective problem of single-use plastic waste pollution.